AB0923 Meeting the fibromyalgia criteria has a negative impact on tnf inhibitors efficacy in patients with axial spondyloarthritis. (15th June 2017) - Dantu, A; Michaud, J; Prieur, M Gauthier; Silva, F Da; Pouplin, S; Lequerre, T; Vittecoq, O; Verdet, M
Abstract : Background: Fibromyalgia and spondyloarthritis can coexist and the overlap between the two diseases could have consequences on TNF inhibitors efficacy. Objectives: To evaluate TNF inhibitors efficacy in patients with axial spondyloarthritis fullfilling or not fibromyalgia criteria. Methods: Prospective observational bicentric study on 25 patients who met ASAS 2009 axial spondyloarthritis criteria. Fibromyalgia was defined by ACR 2010 fibromyalgia criteria or by a ≥5/6 score of the Fibromyalgia Rapid Screening Tool. Following items were recorded before and after a 6 months treatment with TNF inhibitors: Visual Analog Scale for pain and for patient global disease activity, values of ESR and CRP, number of tender joints, MASES score, number of Yunus tender points. All patients filled a self-questionnaire with BASDAI, BASFI, FiRST and ACR 2010 fibromyalgia scale items using SSS and WPI. Criterion of judgment: an ASAS partial remission state was compared in patients with or without fibromyalgia. Results: Of the 25 patients enrolled, 15 (60%) fulfilled ACR 2010 fibromyalgia criteria and 9 (36%) had a ≥5/6 FiRST score. The proportion of patients fulfilling an ASAS partial remission state was significantly lower in patients with fibromyalgia according to the ACR 2010 criteria (20% vs 70%, p=0, 034) or to the FiRST score (0% vs 62, 5%, p=0, 0028). These patients had more severe disease activity and physical fonction than the patients without fibromyalgia. In this study, some factors were related with absence of ASAS partial remission: female gender, prior TNF inhibitor failure, ACR 2010 fibromyalgia criteria positivity, to have more than 11 Yunus points and to have a ≥5/6 FiRST score. Conclusions: Meeting the fibromyalgia criteria might have an impact on ASAS partial remission state and on efficacy of TNF inhibitors in patients with axial spondyloarthritis. The FiRST score was more specific to predict an absence of ASAS partial remission than the ACR 2010 fibromyalgia criteria. TNF inhibitors should be used with circumspection in case of FiRST score ≥5/6 in patients with axial spondyloarthritis. References: Perrot S., Bouhassira D., Fermanian J., the CEDR (2010) Development and validation of the Fibromyalgia Rapid Screening Tool (FiRST). Pain 150(2):250–256. Wolfe F., Clauw DJ., et al. (2011) Fibromyalgia criteria and severity scales for clinical and epidemiological studies: a modification of the ACR Preliminary Diagnostic Criteria for Fibromyalgia. J Rheumatol 38:1113–1122. Disclosure of Interest: None declared